Knowledge and Implementation of the S3 Guideline on Gestational Diabetes among Gynecologists and Diabetologists Four Years after Publication - Groten, T.; Schmitz, S.; Schippert, C.; Schleußner, E.; Hillemanns, P.; Lehmann, T.; von Versen-Höynck, F. (Geburtshilfe und Frauenheilkunde, 2016)
Background: An S3 guideline on the diagnosis and differentiated management of gestational diabetes (GDM) was published in Germany in 2011. This guideline replaced the previously applicable recommendations for the diagnosis and treatment of GDM and, for the first time, compiled evidence-based recommendations for the care of patients with GDM. The new guideline has focused particularly on the counselling offered to all patients with GDM about the associated long-term health risks. In this study we investigated the state of knowledge about the guideline among gynecologists and diabetologists in Thuringia and Lower Saxony. Method: A questionnaire with 23 questions was sent out to 773 gynecologists and 76 diabetologists providing outpatient care in Lower Saxony and Thuringia. The statistical analysis was descriptive and inferential for comparisons between groups. Results: The response rate was 54 %; an average of 47.6 % of the individual questions were answered correctly in the completed questionnaires. The questions were answered correctly significantly more frequently by persons in the group with a good knowledge of the guidelines (75 vs. 61 %, p < 0.001). There were no significant differences between groups when differences between federal states or medical specialties were compared. Conclusions: The results of our study show a good general state of knowledge of the guideline and point to a high level of willingness to implement the recommendations of the S3 guideline on GDM. With regard to the follow-up care provided to patients with GDM and depression, this study found a significant need for further training.
Keywords: gestational diabetes; S3 guideline; diagnosis; treatment; knowledge